Heterologous production of extreme alkaline thermostable NAD+-dependent formate dehydrogenase with wide-range pH activity from Myceliophthora thermophila - Altas, Nilay; Aslan, Askin Sevinc; Karatas, Ersin; Chronopoulou, Evangelia; Labrou, Nikolaos E.; Binay, Baris (Elsevier Sci Ltd, 2017)
NAD(+)-dependent formate dehydrogenase(s) (EC 1.2.1.2, FDH) catalyzes the interconversion of formate anion to carbon dioxide coupled with the conversion of NAD(+) or NADH. FDHs attract significant attention in biotechnology due to their potential applications in NAD(H)-dependent industrial biocatalysis as well as in the production of renewable fuels and chemicals from carbon dioxide. In the present work, a new FDH from thermophilic fungus Myceliophthora thermophik (MtFDH) was characterized. The gene of the enzyme was synthesised, cloned, expressed in E. colt, as 6His-tagged protein, and purified to homogeneity by metal chelate affinity chromatography. Kinetic analysis suggested that MtFDH exhibits higher catalytic efficiency on NaHCO3 compared to formate. Notable, recombinant MtFDH displays a pH optimum for the conversion of formate anion to carbon dioxide at extreme alkaline pH (pH 10.5). Thermal stability analysis showed that the enzyme displays good thermostability with T-m 48 degrees C. Homology modelling and phylogenetic analysis suggested that the enzyme belongs to the D-specific 2-hydroxy acid dehydrogenases family. The active-site residues are well conserved compared to other homologous FDHs. The results of the present work provide new knowledge on the structure, function and diversity of FDHs and indicate that MtFDH possess a huge potential for CO2 reduction or NADH generation and under extreme alkaline conditions.
Keywords: Myceliophthora thermophila; NAD(+)-dependent formate dehydrogenase; Heterologous production; Extreme alkaline; Computational modeling; NADH regeneration; CO2 reduction